2023
DOI: 10.3390/app13105967
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 13 Banned Colorants in Cosmetics via Liquid Chromatographic and Mass Spectrometric Techniques

Abstract: Even though synthetic colorants can cause side effects such as allergies and pigmentation, they have not been sufficiently researched. Herein, high-performance liquid chromatography, liquid chromatography-tandem mass spectrometry, and liquid chromatography-quadrupole time-of-flight mass spectrometry (LC-Q-TOF-MS) were used to detect 13 banned synthetic colorants in cosmetics and characterize their fragmentation. The developed HPLC method was validated following the International Conference on Harmonisation gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The MS fragmentation patterns, confirmed via LC-Q-TOF-MS (performed using an Agilent 1290 Infinity II LC system (Agilent Technologies, Santa Clara, CA, USA) coupled with an Agilent 6545XT Q-TOF-MS system (Agilent Technologies, Santa Clara, CA, USA)), of 11 out of 13 prohibited dye species were reported by Han et al [ 90 ] for the first time, and among the 120 cosmetic samples, one was found to contain three illegal compounds: Basic Blue 26, Basic Red 2, and Basic Yellow 28. Thus, the work of Han et al [ 90 ] shows future promise in view of more rigorous screening and control of the presence of illegal ingredients in cosmetic products and to hinder/restrain their distribution.…”
Section: Ms Analysis Of Cosmetic Ingredientsmentioning
confidence: 78%
See 1 more Smart Citation
“…The MS fragmentation patterns, confirmed via LC-Q-TOF-MS (performed using an Agilent 1290 Infinity II LC system (Agilent Technologies, Santa Clara, CA, USA) coupled with an Agilent 6545XT Q-TOF-MS system (Agilent Technologies, Santa Clara, CA, USA)), of 11 out of 13 prohibited dye species were reported by Han et al [ 90 ] for the first time, and among the 120 cosmetic samples, one was found to contain three illegal compounds: Basic Blue 26, Basic Red 2, and Basic Yellow 28. Thus, the work of Han et al [ 90 ] shows future promise in view of more rigorous screening and control of the presence of illegal ingredients in cosmetic products and to hinder/restrain their distribution.…”
Section: Ms Analysis Of Cosmetic Ingredientsmentioning
confidence: 78%
“…Using sequential steps based on HPLC, LC-MS/MS, and LC-Q-TOF-MS, in Han et al [ 90 ], 13 banned synthetic colorants were detected and structurally characterized (Basic Blue 26, Basic Red 2, Disperse Brown 1, Disperse Orange 3, Disperse Yellow 3, HC Blue No. 2, HC Yellow No.…”
Section: Ms Analysis Of Cosmetic Ingredientsmentioning
confidence: 99%